(3OjhGf GHf GdNWjH OGQjGs - (3eMeO Hf CMeO Hf SdjeGf Hf jYbhH GdCfUGQj GdNRQLj, GdOeTbj GdHjSGfj ; GHf GdNWjH OGQjG,J (B810 (3g` s
(3ChdgG (B:s
(3bGd TjNfG CMeO Gddge Ydi fYe ChdgG dOqj fXe GdbQjV hChd bUGFO GdOjhGf(B: (3CCf dGM ef HQb GdMLGR VjGA YQGc Mfjf RGFO hHcGA s
(3BNQgG (B:s
(3ef cdGe cJHg Ydi bUGFO fHhjI Gddge CeJfG eSdejf, hGMTQfG aj LedI GdYdeGA GdYGedjf hCONdfG aj TaGYI SjO GdeQSdjf Udi Gddg Ydjg hYdi CUMGHg CLeYjf s
(3GdfSNI oeUMMI hHYV GdbUGFO eDQNIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B277 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B266s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B3 - (3U (B98 s
(3eUOQ GbJfGA GdCUd (B:s
(3GdNRGfI GdYGeI HGdQHGW (B(225 (3b(B) s
Keywords: (3GdCOHs